The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1007/s11250-008-9174-x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cytokines and respiratory burst activity of milk cells in response to Azadirachta indica during bovine mastitis

Abstract: The immuno therapeutic potential of hydro-methanolic extract of Azadirachta indica (A. indica) was studied during bovine clinical mastitis (CM). The somatic cell count (SCC), total bacterial count (TBC), milk differential leukocyte count (DLC), hydrogen peroxide (H(2)O(2)), superoxide anion (O(2) (-)) production and interleukin- 2 (IL-2) and gamma interferon (IFN-gamma) cytokines expression were studied before and after intramammary infusion of A. indica extract in diseased cows. The results revealed that A. i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…It has been demonstrated that LPS can effectively induce mastitis in mouse and bovine models [23][24][25]. LPS can induce the production of cytokines, and these cytokines can amplify the inflammatory response in mastitis [26]. It has been suggested that TNF-a, IL-1b, IL-6 and RANTES play an important role in mastitist pathogenesis [27].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that LPS can effectively induce mastitis in mouse and bovine models [23][24][25]. LPS can induce the production of cytokines, and these cytokines can amplify the inflammatory response in mastitis [26]. It has been suggested that TNF-a, IL-1b, IL-6 and RANTES play an important role in mastitist pathogenesis [27].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is also considered to be a characteristic of many human diseases, such as diabetes, cardiovascular disorders, cancers, and arthritis [4]. Most of the important signaling pathways, including the TLR4/MYD88 pathway, PI3K-AKT pathway, MAPK pathway, NF-jB pathway, and the TNF pathway, are all related to inflammation regulation [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Reduced phagocytic activity and production of reactive oxygen species by milk cells after parturition has been described to correlate with a negative metabolic and energy balance that directly affects neutrophil function and increases the risk of mastitis in dairy cows (Cai et al 1994;Hoeben et al 2000). Similar findings were also observed in bovine mastitis (Mukherjee et al 2005;De and Mukherjee 2009). However, phagocytic activity (42.20%), hydrogen peroxide production (29.46%) and myeloperoxidase (49.27%) enzyme activity increased significantly (P < 0.05) in subclinical mastitis-infected quarters following intramammary treatment with amoxicillin plus sulbactam.…”
Section: Discussionmentioning
confidence: 83%